Split-cavity tuning of a rectangular axion haloscope operating around 8.4 GHz - Golm, Jessica; García-Barcelo, Jose María; Arguedas Cuendis, Sergio; Calatroni, Sergio; Wuensch, Walter; Dobrich, Babette (Frontiers in Physics, 2024)
The axion haloscope is the currently most sensitive method to probe the vanishingly small coupling of this prominent Dark Matter candidate to photons. To scan a sizeable axion Dark Matter parameter space, the cavities that make up the haloscope need to be tuned efficiently. In this article, we describe a novel technique to tune axion haloscopes around 8.4 GHz in a purely mechanical manner without the use of dielectrics. We achieve tuning by introducing a gap along the cavity geometry. A quality factor reduction of less than 20 % is achieved experimentally for a tuning range of around 600 MHz at room temperature and at cryogenic temperatures for around 300 MHz. A larger tuning range would require an improved alignments mechanism. We present the results of a corresponding prototype and outline prospects to further develop this technique.